Perilaku Masyarakat dalam Penanganan Malaria - Kody, Martha Meti (JURNAL KESEHATAN PRIMER, 2022)
Backgrond: Malaria is the fourth leading cause of death in the world, after respiratory infections (ISPA), HIV/AIDS, and diarrhea, among the top 10 tropical diseases. Malaria is a significant health problem in the province of East Nusa Tenggara (NTT), where almost 100% of the region is endemic to malaria (NTT Health Office, 2018), particularly in East Sumba Regency. According to data from the Waingapu Health Center, Mbatakapidu Village ranked first in malaria cases in East Sumba Regency in 2022, with 135 cases. The number of malaria cases in the village has increased from 2019 to 2022, with 6 cases in 2019, 6 cases in 2020, 55 cases in 2021, and 135 cases in 2022. This increase is partly due to the community's habit of being outside at night and sleeping without using mosquito nets. Objective: This study aims to assess the community's behavior in malaria prevention in Mbatakapidu Village. Method: The sampling technique used was purposive sampling, with 30 samples. The instrument used was a questionnaire. Results: The results of the study show the behavior (knowledge, attitudes, and actions) of the respondents, with 10.6% exhibiting fair behavior, 73% exhibiting good behavior, and 15.3% exhibiting poor behavior.